Ribble-Rabble, Designing for uncertainty in turn-based battle systems in multiplayer video games - Berglind, Jesper; Dalsmyr, David (My University, 2022)
Uncertainty is a human felt experience which can both be positive and negative, and has been identified through research as an important part for enjoyment in games of all kinds. As uncertainty can be a positive but also a negative feeling, it is therefore important that the uncertainty in a game is properly designed to improve player experience. This project examined how different sources of uncertainty affected player experience in turn-based battle systems in multiplayer video games, and tried to identify key elements in creating an enjoyable experience. A digital prototype featuring a multiplayer battle-system called "Ribble-Rabble" was developed to explore and test these elements. The insights gained from testing the elements were used to produce a set of guidelines with considerations for elements belonging to each source. The project also identified one additional source of uncertainty that had not been previously described.
Keywords: computer, science; engineering; game design; interaction design; project; thesis; uncertainty; user experience